Az egészségügyi dolgozók munkajogi felelőssége az egészségügyi szolgáltatás nyújtásával összefüggésben a betegnek okozott kárért - Marsi, Edit; Kiss, János Márk (Debreceni Jogi Műhely, 2015)
The doctor-patient relationship requires set rules for liability considering the nature of professional norms on medicine and the protection of human life and health. According to these rules, the healthcare provideris vicariously liable for damages suffered as a consequence of healthcare servicesprovided to the patient. In such cases– on the grounds of labor law rules – the healthcare providermay transfer liability to its employee. Considering recent amendments of labor law regulations, it is essential to summarize and analyze relevant labor law norms relatedto medical liability. The employee’s liability for damages is based on the employment relationship between the healthcare provider and the employee. Despite of the healthcare provider’s liability for damages, the employee’s liability is always personal. According to the new labor code the employee’s liability for damages is only ascertainable if the tortfeasor did not act like a reasonable person would have actedunder given circumstances. This means that the tortfeasor’sintention or negligence is irrelevant in the course of ascertaining liability. The purpose of our study is to provide a review of the strict measure of due care in health care services, and to summarize rules about the healthcare professional’s liability for damages.